Vibrations of Impurity Iron Ions in Fluorides (The Peerian Journal, 2022)
In this work, temperature measurements of the gamma-resonance spectra of iron-57 isotopes were carried out. It is determined that the local Debye temperature for the replacement of iron ions in CaF2 is two times higher than that of SrF2.